Validity of Oxygen-Ozone Therapy as Integrated Medication Form in Chronic Inflammatory Diseases - Bocci, Velio; Zanardia, Iacopo; Valacchi, Giuseppe; Borrelli, Emma; Travagli, Valter (Cardiovascular & Haematological Disorders - Drug Targets, 2015)
The state-of-the-art of oxygen-ozone therapy is now clarified and all the mechanisms of action of medical ozone are within classical biochemistry and molecular biology. The outcomes of standard treatments in peripheral arterial occlusive disease (PAOD) and dry-form of age-related macular degeneration (AMD) have been compared with the documented therapeutic results achieved with ozonated autohemotherapy (O-AHT). On the other hand, the clinical data of O-AHT on stroke remain indicative. As the cost of O-AHT is almost irrelevant, its application in all public hospitals, especially those of poor Countries, would allow two advantages: the first is for the patient, who will improve her/his conditions, and the second is for Health Authorities burdened with increasing costs. The aim of this paper is to report to clinical scientists that O-AHT is a scientific-based therapeutic approach without side effects. The integration of O-AHT with effective approved drugs is likely to yield the best clinical results in several chronic inflammatory diseases.
Keywords: chronic obstructive pulmonary disease